Guided Imagery Relaxation: Therapy to Reduce Anxiety Level Before Competing Pencak Silat Athletes - Melly Kar Bella; Isna Hikmawati (Proceedings Series on Health & Medical Sciences, 2022)
Background: Pencak Silat athletes have high emotional reactions in competing so that anxiety will arise in these athletes. Guided imagery (GI) is a technique that relies on descriptive language to facilitate auditory visualization of calming images with the aim of achieving a relaxation response. Objective: To determine the effect of guided imagery relaxation therapy on anxiety before competing in pencak silat athletes in Tapak Suci. Methods: Experimental research with a pre-experimental design (one group pretest-posttest). The research instrument used the Hamilton Rating Scale for Anxiety (HRS-A). The sampling technique used total sampling with the number of respondents as members of pencak silat as many as 30 people from the University of Muhammadiyah Purwokerto silat. Results: The level of anxiety before the match in the moderate category was mostly 46.7% and severe anxiety was 30%, and after being given therapy most of them did not experience anxiety as much as 46.7% and mild anxiety as much as 43.3%. There is an influence of guide imagery on anxiety before competing in pencak silat athletes at the University of Muhammadiyah Purwokerto with a p-value of 0.001 (<0.05). Conclusion: The importance of non-pharmacological therapy to reduce anxiety before competition, so that match readiness is more optimal.